Implementasi Soft Starting Abb Pstx 570 Motor Tiga Phasa Mesin Hammermill di PT.Central Proteina Prima,Tbk - Roza, Indra -; Irsan Pasaribu , Faisal; Adam, Muhammad (JOURNAL OF ELECTRICAL AND SYSTEM CONTROL ENGINEERING, 2023)
In industry, electric motors play an important role as energy for motion in equipment in the production process. During the starting process, it can draw currents up to 5 to 7 times the nominal current when working normally. So that it can have a bad effect on the electric motor and the surrounding electrical equipment. The method that uses the ABB PSTTX 570 Soft Starting is through the method of starting an electric motor using a thyristor circuit. The soft start method is suitable for cars that are quite powerful. The purpose of the soft start method is to obtain a smaller starting current, to reduce the impact of large peak currents during the starting process and to achieve a constant rated speed. In this method, the current in the motor flows slowly during starting until it reaches the rated value within a certain period of time certain. Soft starting measurable display when motor voltage is 34%, moor current is 7.3 A active power is 0.14 kW when motor voltage is 70% motor current is 1782.5 A with active 371.09 kW and when motor voltage is 100% up motor 111.6 A with an active power of 23.65 kW. In terms of size, the advantage of the soft starter is that it is simpler than the inverter starting equipment.